The detection of glyphosate and glyphosate-based herbicides in water, using nanotechnology - De Almeida, Louise Kashiyavala Sophia (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
Glyphosate (N-phosphonomethylglycine) is an organophosphate compound which was developed by the Monsanto Company in 1971 and is the active ingredient found in several herbicide formulations. The use of glyphosate-based herbicides in South Africa for the control of alien invasive plants and weeds is well established, extensive and currently unregulated, which vastly increases the likelihood of glyphosate contamination in environmental water systems. Although the use of glyphosate-based herbicides is required for economic enhancement in industries such as agriculture, the presence of this compound in natural water systems presents a potential risk to human health. Glyphosate and glyphosate formulations were previously considered safe, however their toxicity has become a major focal point of research over recent years. The lack of monitoring protocols for pesticides in South Africa is primarily due to limited financial capacity and the lack of analytical techniques.
Keywords: Water -- Glyphosate content; Aquatic herbicides -- South Africa; Aquatic herbicides -- Physiological effect; Nanotechnology; Invasive plants -- South Africa; Genetic toxicology; Thiazoles; Tetrazolium; Immunotoxicology; Colorimetry; Nanofibers